BATCH AND FLOW-INJECTION SPECTROPHOTOMETRIC DETERMINATION OF SODIUM CEFOTAXIME IN PHARMACEUTICAL PREPARATIONS - Al-Abachi, Mouyed; Al-Ward, Hind; Mohammad, Yassmin (Iraqi Journal of Science, 2024)
Simple and sensitive batch and Flow-injecton spectrophotometric methods (FIA)for the determination of Sodium Cefotaxime in pure form and in injections wereproposed. These methods were based on a diazotization and coupling reactionbetween diazotized Sodium Cefotaxime and thymol in alkaline medium to form anintense red water-soluble dye that is stable and has a maximum absorption at 522nm. A graphs of absorbance versus concentration show that Beer’s law is obeyedover the concentration range of 8-160 and 50-2500 μg.ml-1 of Sodium Cefotaxime,with detection limits of 1.56 and 1.32 μg.ml-1 of Sodium Cefotaxime for batch andFIA methods respectively. The FIA procedure sample throughput was 65 h-1. Alldifferent chemical and physical experimental parameters affecting on thedevelopment and stability of the colored product studied and the proposed methodswere applied successfully on the determination of Sodium Cefotaxime injectionspreparations.